HIV Risk Among Adolescent Girls and Young Women in Age-Disparate Partnerships: Evidence From KwaZulu-Natal, South Africa. (1st June 2018) - Maughan-Brown, Brendan; George, Gavin; Beckett, Sean; Evans, Meredith; Lewis, Lara; Cawood, Cherie; Khanyile, David; Kharsany, Ayesha B. M.
Abstract : Background: Evidence on the role of age-disparate partnerships in high HIV-infection rates among young women in sub-Saharan Africa remains inconclusive. This study examined the HIV-infection risk associated with age-disparate partnerships among 15- to 24-year-old women in a hyperendemic setting in South Africa. Methods: Face-to-face questionnaire, and laboratory HIV and viral load data were collected during 2014–2015 among a representative sample (15–49 years old) in KwaZulu-Natal. The association between age-disparate partnerships (age difference ≥5 years) and HIV status among 15- to 24-year-old women (N = 1459) was assessed using multiple logistic regression analyses. Data from the male sample on all on-going partnerships (N = 1229) involving 15- to 24-year-old women were used to assess whether young women's age-disparate male partners were more likely to have a viral load ≥1000 copies per milliliter, a marker of HIV-infection risk. Results: Women reporting an age disparity in any of their 3 most recent partnerships were more likely to test HIV positive compared to women with only age-similar partners [adjusted odds ratio (aOR): 1.58, 95% confidence interval (CI): 1.20 to 2.09, P < 0.01]. Among partnerships men reported with 15- to 24-year-old women, the age-disparate male partners were more likely to be HIV positive and have a viral load ≥1000 copies per milliliter (aOR: 2.05, 95% CI: 1.30 to 3.24, P < 0.01) compared with age-similar partners. Results were similar for each category of age disparity: partners 5–9 years older (aOR: 2.01, 95% CI: 1.18 to 3.43, P = 0.010) and those ≥10 years older (aOR: 2.17, 95% CI: 1.01–4.66, P = 0.048). Conclusions: Results indicate that age-disparate partnerships increase young women's HIV risk, although conclusive evidence was not ascertained. Interventions addressing risk from age-disparate sexual partnering, including expanding antiretroviral treatment among older partners, may help to reduce HIV incidence among young women. Abstract : Supplemental Digital Content is Available in the Text.